Sustainable groundwater extraction for agriculture use at Bukit Merah Aquifer in Semanggol, Perak, Malaysia - Makzin, Norfaezah (2020)
Sufficient water supply is required by paddy plants at all growth stages for high yields. Although Malaysia receives an annual rainfall of about 3,000 millimeters, which is above the global average, climate change such as El-Nino can influence the amount of rainfall leading to prolong drought. The uncertainty of climate patterns and the high dependency of the country on surface water resources have worsened the water supply situation. Paddy cultivation around the district of Kerian which obtains irrigation sources from Bukit Merah Dam was severely affected during the phenomenon. Surface water that is easily affected by climate change causes water supply crisis and inability to supply the irrigation source. Therefore, an alternative source of groundwater that could be extracted needs to be studied to have sustainable supply of water for agricultural purposes. The main objective of this study was to evaluate the sustainable groundwater extraction for agriculture use in Bukit Merah, Semanggol, Perak. The groundwater model was developed using Visual MODFLOW to simulate sustainable groundwater extraction without environmental effect. The lithological formation of the study area was constructed using wells information and assisted with resistivity survey using pole-dipole arrangement. The electrical resistivity tomography (ERT) profile was interpreted with reference to geological map to determine the types of rocks that underlie the area. A 4-layer model was developed to represent the lithological formation of the study area; unconsolidated deposit, sedimentary, metamorphic, and granite layer. Then, the conceptual model was built using geological and hydrogeological data of the study area. The model was calibrated to acceptable limits for head observation and chloride concentration. The simulation was done under different pumpings for both normal and extreme-low groundwater recharges. The impact of groundwater extraction on the river and lake system during normal and dry season was assessed. The groundwater flow pattern, groundwater balance and saltwater interface were determined by simulating in-steady state of groundwater flow. This study has revealed that the sustainable groundwater extraction during normal groundwater recharge is 80,000 m3/day and 50,000 m3/day during extreme-low groundwater recharge respectively without any negative impacts on groundwater resource and surrounding ecosystem. In conclusion, throughout the development of groundwater resources in the area, it could be utilized by the farmers around the Kerian area for irrigation purposes especially during droughts.